A centralized multilayer LPV/H∞ control architecture for vehicle's global chassis control, and comparison with a decentralized architecture. Issue 2 (2020) - Hamdan, A.; Chokor, A.; Talj, R.; Doumiati, M.
Abstract: This paper deals with the development of Global Chassis Controller where the Active Front steering, Direct Yaw Control and Active Suspensions, are coordinated together in the aim to improve the overall vehicle performance i.e maneuverability, lateral stability and rollover avoidance. The main contribution of this work is the integration of the Active suspension system (AS) in a centralized multilayer control architecture to control the roll angle. A polytopic approach is used to find the LPV/H∞ controller where an offline Linear Matrix Inequality (LMI) optimal solver is used to realize the optimality of this controller. The different layers of this architecture are detailed. The proposed LPV/H∞ controller is validated by simulation using Matlab/Simulink, and a comparison is done with a decentralized architecture that has been developed in the laboratory, to show the difference in behavior and performance of both strategies of control and the effectiveness of centralized one on the rollover avoidance.